La educación para la ciudadanía en España desde la LODE y la LOGSE al Anteproyecto de LOE. Algunas propuestas para la programación y los profesores - Cobo Suero, Juan Manuel (Miscelánea Comillas, 2005)
Toward the end of 2004 the Ministry of Education and Science of Spain opened a debate in preparation for a forthcoming law on education. The first part of this article studies the approach of one of the themes of this debate —education for citizenship— in the educational system of Spain at present, from theLODE (1985) and the LOGSE (1990) until the draft or draught of LOE (March 2005 ). Since this matter requires new programs and preparation of the faculty, the second part of the article presents some contributions to these latter concerns.